Hardness of the habitual diet and its relationship with cognitive function among 70‐year‐old Japanese elderly: Findings from the SONIC Study - Okubo, Hitomi; Murakami, Kentaro; Inagaki, Hiroki; Gondo, Yasuyuki; Ikebe, Kazunori; Kamide, Kei; Masui, Yukie; Arai, Yasumichi; Ishizaki, Tatsuro; Sasaki, Satoshi; Nakagawa, Takeshi; Kabayama, Mai; et al. (Journal of oral rehabilitation, 2019)
Summary Background There is increasing evidence of causal links between poor mastication and cognitive impairment, but possible effects of dietary hardness, which clearly affects mastication, on cognitive function are unknown. Objective We investigated the hypothesis that hardness of the habitual diet would be associated with cognitive function among older Japanese adults. Methods The subjects of this cross‐sectional study were 635 Japanese community‐dwelling people aged 69‐71 years. The masticatory muscle activity required for the habitual diet was used to determine dietary hardness. Consumption of 38 foods was assessed by a validated, brief‐type, self‐administered diet history questionnaire. A published database was then used to estimate the masticatory muscle activity involved in the ingestion of these foods. The Japanese version of the Montreal Cognitive Assessment (MoCA‐J) was used for the measurement of cognitive function. Results The principal contributors to dietary hardness were cooked rice (28.0%), green leafy vegetables (5.1%), dried fish (4.9%), and pork and beef (4.6%). There was a positive association between dietary hardness and MoCA‐J score that was robust to adjustment for potential confounders (MoCA‐J score per 100‐unit increase in dietary hardness: β = 0.83 [95% CI: 0.08, 1.59], P = 0.03). These results did not change materially even after exclusion of subjects who reported substantial changes in their diet for any reason (β = 0.94 [95% CI: 0.02, 1.86], P = 0.04). Conclusion This preliminary cross‐sectional study suggests that dietary hardness might have a beneficial effect on cognitive function in older Japanese people. Further prospective studies with more accurate measurements are needed to confirm this finding.